Seed priming to enhance spinach (Spinacia oleracea L.) germination at supraoptimal temperature = Priming de semillas para mejorar la germinación de espinaca (Spinacia oleracea L.) a temperatura supraóptima - Breit, A. (2025)
Spinach germination is affected by soaking temperature above 20 °C. An experiment was conducted to study the effect of different priming treatments on germination of spinach at 15 and 20 °C. Two osmotic agents for priming were studied: CaCl2 and polyethylene glycol 6000 (PEG). Biopriming with Azospirillum brasliense bacteria (3 × 108 UFC mL−1) was performed on half of seeds previously primed with osmotic agents. Three spinach cultivars were used in the experiments: Amadeo, Super Dorrego and Ibis. The experimental layout was completely randomized with five replicates per treatment. At 15 °C germination percentage (GP) of primed seeds increased by approximately 30 %. At 20 °C primed seeds increased GP more than 50 %. At both germination temperatures, biopriming did not allow a greater GP increase compared to seeds only primed with osmotic agents.